Interdependencies between mining costs, mining rewards and blockchain security - Pavel Ciaian; D'Artis Kancs; Miroslava Rajcaniova (Economics and Econometrics Research Institute (EERI), 2021)
This paper studies to what extent the cost of operating a proof-of-work blockchain is intrinsically linked to the cost of preventing attacks, and to what extent the underlying digital ledger's security budgets are correlated with the cryptocurrency market outcomes. We theoretically derive an equilibrium relationship between the cryptocurrency price, mining rewards and mining costs, and blockchain security outcomes. Using daily crypto market data for 2014-2021 and employing the autoregressive distributed lag approach - that allows treating all the relevant moments of the blockchain series as potentially endogenous - we provide empirical evidence of cryptocurrency price and mining rewards indeed being intrinsically linked to blockchain security outcomes.
Keywords: D82; E42; G12; G15; G18; G29; 330; Cryptocurrency; ARDL; blockchain; proof-of-work; security budget; institutional governance technology; network externalities